How to prestress compliant mechanisms for a targeted stiffness adjustment. (3rd July 2020) - Mauser, Kristian; Hasse, Alexander
Abstract: The paper deals with compliant mechanisms with a variable stiffness behavior. Devices with such a behavior are getting more and more attention in recent years, especially in contact applications such as human-robotic-interactions or haptic interfaces. In the work presented here the variable stiffness behavior is achieved by the targeted application of prestressing forces. An optimization based method is presented to identify suitable force application points. Furthermore, the amount and direction of force is determined in order to cause a specific change in stiffness. The method consists of a convex optimization formulation and is based on modal parameters. The method is intended to work for any given design of a compliant mechanism. In this publication the method is tested and evaluated using two compliant mechanisms—the cartwheel hinge and a shape-adaptive airfoil profile.